Effects of Bifidobacterium longum Subsp. infantis CECT 7210 and Lactobacillus rhamnosus HN001, Combined or Not With Oligofructose-Enriched Inulin, on Weaned Pigs Orally Challenged With Salmonella Typhimurium - Rodríguez-Sorrento, Agustina; Castillejos, Lorena; López-Colom, Paola; Cifuentes-Orjuela, Gloria; Rodríguez-Palmero, Maria; Moreno-Muñoz, José Antonio; Martín-Orúe, Susana María (Frontiers in Microbiology, 2020)
Salmonella is a common causative agent of enteric disease and is developing mechanisms of resistance to antimicrobials. Probiotics, such as bifidobacteria and lactobacilli, and prebiotic fibers are a potential alternative to counteract this pathogen as they have demonstrated effectiveness in preventing its adhesion, reducing intestinal damage, and enhancing the host immune system. Furthermore, the benefits are expected to be potentiated when these compounds are administered together. A trial was performed to evaluate the efficacy of two probiotic strains (Bifidobacterium longum subsp. infantis CECT 7210 (Laboratorios Ordesa S.L.) and Lactobacillus rhamnosus HN001, combined or not with a prebiotic containing oligofructose-enriched inulin, against Salmonella Typhimurium. Ninety-six pigletswere distributed into 32 pens assigned to 5 treatments: one non-challenged (control diet, CTR+) and four challenged: control diet (CTR-) or supplemented with probiotics (PRO), prebiotic (PRE), or their combination (SYN). After 1 week, animals were orally challenged with Salmonella Typhimurium. Feed intake, weight, and clinical signs were recorded. On days 4 and 8 post-inoculation (PI), one animal per pen was euthanized, and samples from blood, digestive content, and ileal tissues were collected to determine Salmonella counts, fermentation products, ileal histomorphology, and serum TNF-α and Pig-MAP concentrations. The effect of the oral challenge was evidenced by animal performance, fecal consistency, and intestinal architecture. Regarding the experimental treatments, animals of PRO group experienced a faster clearance of the pathogen, with more pigs being negative to its excretion at the end of the study and recovering the impaired ileal villi/crypt ratio more rapidly. Animals receiving the PRE diet showed a lower intestinal colonization by Salmonella, with no countable levels in any of the analyzed samples, and an augmented immune response suggested by serum Pig-MAP concentrations. Treatments including the prebiotic (PRE and SYN) showed similar changes in the fermentation pattern, with an increase in the molar percentage of valeric acid concentration in colon. The SYN group, however, did not show any of the outcomes registered for PRO and PRE in Salmonella colonization or in immunity markers, suggesting the lack of synbiotic action in this animal model. Further research is needed to better understand the complex mechanisms behind these effects.